Matrix-Associated Chondrocyte Implantation Is Associated With Fewer Reoperations Than Microfracture: Results of a Population-Representative, Matched-Pair Claims Data Analysis for Cartilage Defects of the Knee. Issue 10 (17th October 2019) - Niemeyer, Philipp; Schubert, Tino; Grebe, Marco; Hoburg, Arnd
Background: Symptomatic cartilage defects of the knee are commonly surgically treated by microfracture (MFX) or matrix-associated chondrocyte implantation (M-ACI). Several randomized controlled trials have compared MFX and M-ACI, showing a tendency to lower reoperation rates for M-ACI, but results vary widely between studies. Purpose: To compare reoperation rates after MFX and M-ACI in cartilage defects of the knee outside clinical trials in a representative sample of the population. Study Design: Cohort study; Level of evidence, 3. Methods: This study was based on anonymized, population-representative claims data of 4 million insured persons in Germany. Patients who underwent MFX or M-ACI for cartilage defects of the knee with a follow-up of 2 years were compared. The primary endpoint was the need for a reoperation, defined as a claim for a second surgical procedure from the same patient at the knee joint (27 procedure codes), meniscus and cartilage (35 procedure codes), or patella (102 procedure codes) or the need for knee replacement (11 procedure codes). Group comparisons were performed using log-rank tests, with a 2-sided P value of <.05 to indicate significance. For adjusted analysis, propensity score matching was applied. Age, sex, comedications, and comorbidities were used as matching parameters. Results: A total of 6425 patients fulfilled the inclusion criteria: 6273 treated with MFX and 152 treated with M-ACI (mean age, 53 and 36 years, respectively). In the 2 years after treatment, 1271 patients in the MFX group needed a reoperation compared with 19 in the M-ACI group (20.3% vs 12.5%, respectively; P = .0199). For adjusted analysis after propensity score matching, 127 patients per group were analyzed. Their mean age was 37 years. At the end of the second follow-up year, 28 and 16 patients needed reoperations in the MFX and M-ACI groups, respectively (22.0% vs 12.6%, respectively; P = .0498). Conclusion: This study used a representative sample of the population and a broad definition of a reoperation, thus expanding evidence from clinical trials. We found a significant advantage of M-ACI in reoperation rates 2 years after treatment. After adjusting for age, sex, comedications, and comorbidities, M-ACI still showed significantly lower reoperation rates after 2 years.